Economic Approaches to Ecosystem Analysis - Thomas Eichner; Rüdiger Pethig (Universität Siegen, Fakultät III, Wirtschaftswissenschaften, Wirtschaftsinformatik und Wirtschaftsrecht, 2001)
Ecological systems (ecosystems, for short) are complex systems of interacting species, plants and animals, where each of the species consists of individual organisms that interact with organisms of the same or other species in various ways: they compete for scare resources and they are involved in predator-prey or mutualistic relationships. The challenge to understand the performance and changes of ecosystems over time was taken up long time ago by ecologists. In the ecological literature a vast number of models address ecosystem dynamics, taking populations as the relevant endogenous variables and investigating how populations develop and interact over· time. For brevity, we call them ecological population models. Many of them focus on the simplest case of a single species as an aggregate entity developing over time. The prototype (heuristic) model for one large homogenous population in a constant environment is the logistic growth curve based on the so-called Verhulst-Pearl equation. Pierre Francois Verhulst (1838) introduced the logistic equation and Raymond Pearl (1930) applied it to population growth in the US; this equation turned out to become an important analytical tool in ecosystem analysis...
Keywords: Q50; Q57; 330; ecosystem; organism; species; biomass; population